The IgA of hares (Lepus sp.) and rabbit confirms that the leporids IgA explosion is old and reveals a new case of trans-species polymorphism - Pinheiro, Ana; de Sousa-Pereira, Patrícia; Esteves, Pedro J. (Frontiers in Immunology, 2023)
Background: Immunoglobulin A (IgA) is the mammalian mucosal antibody, providing a major line of defence against pathogens. With 15 IgA subclasses, the European rabbit has the most complex IgA system in mammals, strikingly more complex than most other mammals that have only one IgA, or in the case of hominoids, two IgA subclasses. Similarly, to the two Hominoid primates IGHA genes, the expansion of the rabbit IGHA genes seems to have begun in an ancestral Lagomorph, since multiple IgA copies have been found for Sylvilagus, Lepus, and Ochotona genera, through Southern blot analysis. Results: To gain a better insight of the extraordinary Lagomorph IgA evolution, we sequenced, for the first time, expressed IgA genes for two Lepus species, L. europaeus and L. granatensis. These were aligned with the 15 rabbit IgA isotypes and evolutionary analyses conducted. The obtained phylogenetic tree shows the Lepus IgA sequences clustering with and among rabbit IgA isotypes and the interspecies and intraspecies nucleotide genetic distances are similar. Comparing the amino acid sequences of the Lepus and rabbit IgA confirms that there are two trans-species polymorphisms and that the rabbit and Lepus sequences share a common genetic pool. In, fact the main differences between the studied leporids IgA reside in the hinge region characteristics.The Lepus IgA sequences we have obtained strongly suggest that the great expansion